KEJADIAN DISMENOREA PRIMER PADA SISWI SMAN 5 BEKASI - Meilan, Nessi (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
During the menstrual period, most teenage girls often experience discomfort in the form of stomach cramps, which is pain in the lower part of the stomach which sometimes extends to the waist, back or thighs. Some may even feel nauseous, vomit or have diarrhea too. Dysmenorrhea is a disruption in menstrual blood flow or menstrual pain. More than 50% of women experience dysmenorrhoea and 15% of them experience severe pain. Dysmenorrhea usually occurs during adolescence, which is around 2-3 years after the first menstruation. Dysmenorrhea is the main gynecological problem most often complained of by teenagers (French, 2008). The aim of the research is to determine the factors associated with the incidence of dysmenorrhoea among female students at SMAN 5 Bekasi in 2023. This type of research is cross sectional with a sample size of 66 respondents. This research was conducted in April 2023. Data collected used primary data using a questionnaire. The results of this study show that there is a relationship between nutritional status (p value 0.002), age of menarche (p value 0.048), length of menstruation (p value 0.001), menstrual cycle (p value 0.001) while physical activity (0.078) has no relationship with the incidence of dysmenorrhoea. . The results of this research can be used as a reference so that female teenager can be more active in seeking information about dysmenorrhoea so as to increase knowledge and insight regarding the incidence of dysmenorrhoea so that they can take the most appropriate preventive measures to reduce the pain of dysmenorrhoea during menstruation and its impacts and young women are more prepared and not afraid when facing it. Keywords: Dysmenorrhea, Individual Characteristics, Physical Activity